Model of environmental governance in Kazakhstan - Omarova, A.T.; Jazykbayeva, B.K.; Orynbassarova, Y.D.; Grelo, M.F. (BUKETOV BUSINESS REVIEW, 2018)
The article reveals the main problems in the field of environmental management in the Republic of Kazakhstan. It represents the structure of the functioning of the organizational-economic mechanism of environmental protection based on the management of national policy. Kazakhstan has accumulated a huge number of environmental and social problems that have hampered the development of the country on a stable basis. The country's economic growth is mainly due to rising prices for raw materials on world markets and the use of a significant amount of natural resources. Despite the presence of advanced standards, it is necessary to improve environmental protection legislation, since some of its rules create unnecessarily high administrative barriers to entrepreneurship, a high level of potential corruption, which does not contribute to solving environmental problems. Today, unfortunately, administrative incentives in the environmental behavior of economic entities and other activities dominate in the mechanisms of state regulation of the environment. Tools for market management and social impact on the environment have not yet become widespread, and, as a result, at present, the legal provision of economic incentives for environmental management is ineffective. The current environmental policy of Kazakhstan based on the ecosystem approach is considered. It takes into account the territorial separation of powers and responsibilities between the subjects of management. The object of control is the environment in the Republic of Kazakhstan. The authors also analyze a mixed model for managing sustainable development and environmental protection in Kazakhstan as part of an administrative reform.